SSI-Based Newton’s Laws Flipbook to Enhance Critical Thinking and Science Literacy - Ismi Izzatun Naeli; Ellianawati Ellianawati; Hardimah Mohd. Said (CV FOUNDAE, 2026)
To effectively enhance critical thinking and science literacy in physics, there is a need to use instructional materials that effectively relate concepts to real-life situations. The objective of this study was to design and validate a Newton's Laws flipbook teaching material using Socio-Science Issues (SSI) to enhance critical thinking and science literacy in physics. The ADDIE model was used in this study, which comprised Analyze, Design, Develop, Implement, and Evaluate stages in developing a new instructional material. Experts validated the product, while small- and large-scale tests were conducted using validation sheets, readability tests, pretest-posttest, and questionnaire tests. The results revealed a high level of content validity, with Aiken's V values ranging from 0.85 to 0.89. The readability level of the material was 73.06%, indicating that the material is easy to comprehend. The experimental group scored higher in the N-gain analysis, with a moderate level of critical thinking (0.54) and science literacy (0.48). The teaching material received high practicality ratings from both students (90.04%) and teachers (93.87%). This indicates that SSI-based flipbook materials effectively integrate physics concepts with socio-science issues, which enhance critical thinking and science literacy in students. This study contributes to developing innovative digital teaching materials, and future research should explore its application in other physics topics.